Histological Study of Mosquito Larvae (Aedes caspius) Treated with Essential Oils of Thymus serpyllum and Origanum majorana in the El Oued and El Kala Region - Deb ,Malak.; Zelaci, Nour El Houda. (University of Eloued جامعة الوادي, 2025)
The mosquito Aedes caspius poses a health threat in many areas, including Algeria, where it is widely spread and causes epidemics of vector-borne diseases such as malaria and dengue fever. This study aims to evaluate the efficacy of essential oils extracted from Thyme (Thymus serpyllum) and marjoram (Origanum majorana) in controlling Aedes caspius larvae. Essential oils were extracted using a Clevenger apparatus, with the yield of thyme oil being 1.10% and marjoram oil 0.74%. Toxicity tests were conducted on larvae at different concentrations for 24, 48, and 72 hours. The results showed that both oils had a toxic effect on mosquito larvae, with mortality rates increasing with higher concentrations over the different time periods. The lethal concentrations (LC50 and LC90) of the oils were as follows: marjoram oil (LC50 = 175 µL/L, LC75 = 268.71 µL/L, LC90 = 325 µL/L) and thyme oil (LC50 = 39.62 µL/L, LC75 = 145.02 µL/L, LC90 = 208.26 µL/L). Histological examination revealed faster and stronger destruction of the midgut epithelium and cytoplasmic cells in the larvae treated with thyme oil compared to those treated with marjoram oil. The results suggest that Thymus serpyllum oil is more effective in eliminating Aedes caspius larvae than marjoram oil, supporting the potential use of both oils as natural alternatives for mosquito control.
Biodiversity and Environment
Keywords: Essential oils; Aedes caspius; Toxicity; Histological examination